Evaluation of Spirulina Platensis Crude Extract against some Pathogenic Microorganisms and Determination of Amino Acid Profile by HPLC, Erbil City (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The concept of biological controls and the use of algal extracts as antimicrobial substance has received widespread of attentions over the past few years. Therefore, the present study aimed to determine antimicrobial activities of Spirulina platensis and also Analysis of Amino acid profile by HPLC. For achieve this goal two different organic solvents have been used for extracts of Spirulina platensis, which were ethanol, and ethyl acetate. Crude extract of Spirulina platensis was tested in vitro against Salmonella Typhi (ATCC:14028), Streptococcus pyogenes (ATCC:19165) and Candida albicans (ATCC:10231) with Agar well diffusion method (1\10 W\V), additionally HPLC determined amino acid profile and the protein percentage per dry weight of extract. The results of present study declared that antimicrobial activity of crude extract of Spirulina platensis by ethanol was more effective than ethyl acetate, the highest inhibition zone was recorded against Candida albicans  which was 19.5mm (ethanol solvent) and estimated protein percentage was 18.12 % in dry weight of Spirulina platensis.